The optimal location and sizing of single and multiple statcom using analytical approaches under high loading occasion - Ismail, Bazilah; A. Wahab, Noor I.; Othman, Mohammad L.; M. Radzi, M. A.; Vijayakumar, Kanendra N.; Rahmat, Mohd K.; Naain, Muhammad N. M. (Taylor's University, 2022)
With the advancement of technology, there is a rising demand for electrical power, which has greatly exacerbated the challenges faced by electrical power utilities today. Power transmission networks are being forced to operate at near-critical levels as a result of the deterioration of the aging grid infrastructure. This has the potential to create transmission line tripping, which could eventually result in cascading outages and blackouts. At this point, the voltage level on specific buses falls below the lower voltage limit, resulting in enormous system losses. Thus, developing new transmission networks or expanding current ones is necessary to address the effect of ever-increasing demand. However, this typically requires a significant amount of time and resources. The most effective way to address this issue isto add Flexible Alternating Current Transmission System (FACTS) devices to the current transmission network. Furthermore, an appropriate placement of FACTS in the network is essential to ensuring the investment's viability. In this work, various analytical approaches using Power Loss Index (PLI), Voltage Profile Index (VPI), Voltage Stability Index (PSI) and Loss Sensitivity Factor (LSF) were adopted to validate the most optimal placement of Static SynchronousCompensator (STATCOM) in the power network. The proposed methodologies were evaluated in two distinct benchmark test systems: the IEEE 14 bus and the IEEE 33 bus, taking into account the impact of high loading conditions associated with single and multiple STATCOM(s) integration.